Coordinative versatility in main group complexes of C-2, 6-terphenyl substituted amidinates. (15th September 2019) - Cole, Marcus L.; McKay, Alasdair I.; Ping, Ng Sze
Graphical abstract: Lithium and aluminium amidinate complexes have been prepared from two new C -terphenyl amidines. The solid-state structures of these complexes show significant congestion about the metal centres, which leads to different ligand binding modes and lability of coordinated solvents. Abstract: The synthesis and characterization of two C -2, 6-terphenyl substituted amidines, N, N′ -dicyclohexyl-2, 6-di(4-tolyl)benzamidine and N, N′ -dicyclohexyl-2, 6-dimesitylbenzamidine, are described. Both crystallize as the E-syn isomer, though interconversion between the E - syn and Z - syn isomers is observed for both in solution. These amidines are readily deprotonated by either n -butyllithium in THF or AlMe3 in toluene, affording the THF solvated lithium and dimethylaluminium amidinate complexes respectively. These complexes have been characterized in the solid-state using single-crystal X-ray crystallography. The identity of the 2, 6-substituents on the secondary arene rings of the terphenyl group plays a significant role in the coordination motif adopted by the amidinate, as well as the potential to access bis(amidinato)metal complexes.